Implementasi Nilai-Nilai Pancasila bagi Peserta Didik di Era Globalisasi - Revita Pujiarti; Shinta Suhertina; Muhammad Rizaldi Ardian; Novia Nurul Rahmadani (IJOCE: Indonesia Journal of Civic Education, 2021)
ABSTRACT The purpose of this study is to determine the implementation of Pancasila values ​​for students in the era of globalization. This research method uses a research library (Library Study). The results show that Pancasila has a series of values, namely divinity, humanity, unity, democracy, and justice. The five values ​​are a unified whole which refers to a single goal. The basic values ​​of Pancasila such as divinity, humanity, unity, democracy, and justice are universal, objective, meaning that these values ​​can be used and recognized by other countries. As an ideology of the Indonesian nation and state, Pancasila is essentially not only a result of reflection or thought of a person or group of people as other ideologies in the world, but Pancasila is lifted from traditional values, cultural values ​​and religious values ​​contained in Indonesian people's view of life. The conclusion of the study is that by applying the values ​​of Pancasila for students in the era of globalization, it can be done at the right moment, such as during the commemoration of the Youth Pledge Day, Independence Day, Hero's Day and other national holidays. earnestly with all his abilities for the sake of the good name of the nation and the state, love and be proud without shame in using domestic products for the progress of the country's economy. Keywords: Globalization, Pancasila, Students.